Overview of Smart Contract adoption in South America: Legal infrastructure, projects and initiatives - Micheviz, Rafael; Peinado, Jurandir (Revista de Administração da UFSM, 2025)
Purpose: This article aims to analyze the adoption stage of smart contracts in the most representative South American countries, considering legal, institutional, technological aspects and ongoing practical initiatives. Methodology: The study adopts a qualitative approach, based on documentary and bibliographic research. Legislation, court decisions, bills, governmental and business initiatives in seven South American countries were examined. Data collection involved official primary sources and a structured digital survey. Findings: The findings show that all analyzed countries legally recognize electronic signatures, providing a favorable environment for implementing smart contracts, even in the absence of specific legislation. Brazil stands out with bills under discussion. Colombia, Peru, and Paraguay present significant pilot initiatives in both public and private sectors. Contributions: The study proposes a comparative analytical model that synthesizes the maturity level of smart contract adoption in South America. By articulating legal, institutional, and technological dimensions, the article contributes to academic debate and provides insights for public policy and regulatory harmonization strategies.